The Effect of Calcium Doping on the Surface and Catalytic Properties of Cobaltic Oxide Catalysts - Nasr-Allah M. Deraz (Adsorption Science & Technology)
The effects of calcium oxide doping (0.75, 1.5 and 3 mol% CaO) and calcination temperature (400, 500, 600 and 700°C) on different surface properties of Co 3 O 4 were investigated. The structural properties of pure and doped oxide samples were determined by XRD methods, the textural properties were investigated via the adsorption of nitrogen at −196°C while the hydrogen peroxide decomposition activity of the investigated solids was determined by oxygen gasometric measurement of the reaction kinetics at 20–40°C. The dissolution of calcium ions in the Co 3 O 4 lattice at temperatures in the range 400–600°C was accompanied by a marked decrease in the mean hydraulic radii (r h ) and an increase in the surface area (S BET ) and total pore volume (V p ) of the prepared oxide samples. In contrast, doping at 700°C brought about a decrease in the S BET and V p values of the investigated solids. The catalytic activity for H 2 O 2 decomposition on cobaltic oxide calcined at 400–700°C was found to decrease considerably on doping with CaO. The activation energy for sintering (ΔE s ) of the pure and doped solids was determined from the variation in their S BET values as a function of the calcination temperature of these solids. Calcium oxide treatment resulted in a 50% increase in the activation energy of sintering of cobaltic oxide solid calcined at 400–600°C. This increase reflects the role of CaO doping in hindering the sintering of cobaltic oxide.